Karakteristik Kimia, Sifat Sensori dan Waktu Larut Penyedap Rasa Bubuk Jamur Tiram (Pleurotus ostreatus) dan Tomat (Solanum lycopersicum L.) dengan Metode Foam-Mat Drying - Agustina Khalimatur Rahmah; Nur hidajah; Yunan Kholifatuddin Sya’di (Jurnal Pangan dan Gizi, 2023)
Food additives such as flavoring are ingredients that are often needed by the community for cooking needs. The savory taste or umami taste contained in the flavoring is due to the presence of glutamic acid. Glutamic acid can be derived from natural materials such as oyster mushrooms and tomatoes. The presence of glutamic acid in oyster mushrooms and tomatoes can be used as a flavoring that can give an umami taste.The purpose of this study was to determine the glutamic acid content, water content, salt content, sensory properties, and dissolving time of oyster mushroom and tomato flavoring using the foam mat drying method. In this study, the method used was an experimental design using RAL (Completely Randomized Design) with one factor, namely the formulation of oyster mushrooms and tomatoes.The formulation of oyster mushroom versus tomato used is 70:30. 60:40, 50:50, 40:60, and 30:70. The analysis tested in this study was glutamic acid content, water content, salt content, sensory properties and dissolving time of oyster mushroom and tomato flavoring. The results of this study showed that the flavorings of oyster mushrooms and tomatoes were significantly different on glutamic acid content, water content, salt content, and color but not significantly different on soluble time, taste, aroma and texture. The best treatments for oyster mushroom and tomato flavoring included glutamic acid (17.878 ppm), water content (3.0%), salt content (1.54%), dissolving time (39.19 seconds), and sensory (3,83.) in formulation 1 with a ratio of oyster mushrooms and tomatoes (70:30).